Motivasi Kerja Karyawan Di PT Bio Nusantara Teknologi Bengkulu - Aljihad Chandra Dinata; Evi Lorita; Tuti Handayani (Jurnal Multidisiplin Dehasen (MUDE), 2024)
This study aims to determine employees’ work motivation at PT. Bio Nusantara Teknologi Bengkulu and how PT. Bio Nusantara Teknologi motivates its employees. This research is a qualitative research that is presented descriptively. The research informants totaled 5 people consisting of 1 key informant and 4 main informants. Data collection methods through interviews, observation, and documentation. Based on the results of research and discussion using the theory of employees’ motivation (Baldoni, 2005: 5) there are three indicators used, namely Energize (giving power), Encourage (encouraging), and Exchort (urging). And it can be concluded that employees’ motivation at PT. Bio Nusantara Teknologi Bengkulu has been sufficiently implemented. This can be seen from several indicators, namely: 1) Energize, the motivation carried out by PT. Bio Nusantara Teknologi Bengkulu is to set a good example as a leader, communicate clearly to employees, and provide challenges that can spur employee morale. 2) Encourage, employees at PT. Bio Nusantara Teknologi Bengkulu are given opportunities for career advancement and promotion, given basic training before work and training to improve skills, and get awards for the efforts they make for the progress of the company. 3) Exchort, employees (leaders) of PT. Bio Nusantara Teknologi also make sacrifices to motivate the work of other employees, such as sacrificing time, material, experience, and mentally for the progress of the company and motivating employees or subordinates. Employees of PT. Bio Nusantara Teknologi Bengkulu are given prizes for their contributions to the company which are expected to be an inspiration for other employees. All of this is done so that employees are motivated to work and make employee productivity increase, employees’ performance is getting better and more enthusiastic at work, employees are more committed to the company, and employees will appreciate their work.